Assessment of the method for calculating the Lewis number of H2/CO/CH4 mixtures and comparison with experimental results. (23rd March 2017) - Lapalme, Denis; Lemaire, Romain; Seers, Patrice
Abstract: This paper investigates the various techniques used in the literature to calculate the effective Lewis number of two-component (H2 /CO and H2 /CH4 ) and three-component fuels (H2 /CO/CH4 and H2 /CO/CO2 ) over a wide range of equivalence ratios (0.6 ≤ φ ≤ 1.4) under laminar flame conditions. The most appropriate effective Lewis number formulation is identified through comparison with experimentally extracted Lewis numbers ( Le ). The paper first identifies the proper methodology to extract the experimental Le from the burned Markstein length of an outwardly propagating flame. Second, the different methodologies for the calculation of the effective Le are presented and compared to experimental results for H2 /CH4 and H2 /CO mixtures. Based on the experimental results, it is shown that the calculation of the effective Le of mixtures can be divided into a three-step procedure depending on the equivalence ratio: (1) calculation of the Le for each fuel and the oxidizer; (2) use of the Le mixing rule; and (3) assessment of the necessity or not of combining the fuel's and oxidizer's Lewis numbers. The paper shows that, in rich mixtures, the oxidizer Le needs to be taken into account. Lastly, the methodology is validated for H2 /CO/CH4 and H2 /CO/CO2 fuels. Highlights: Effective Lewis number formulations for multicomponent fuel mixtures are assessed. The volume-based mixing rule was found to be the most accurate for all considered blends. The combination of fuel and oxidizer Le is required solely in near-stoichiometric mixtures.